The performance of transmission pipelines on february 6th, 2023 Kahramanmaras earthquake: a series of case studies (jul, 10.1007/s10518-024-01957-2, 2024) - Uckan, E.; Aksel, M.; Atas, O.; Toprak, S.; Kaya, E. S. (Springer, 2025)
[No abstract available]